The location of Oort Cloud comets C/2011 L4 Panstarrs and C/2012 S1 ISON on a comet evolutionary diagram (2014)
ABSTRACT: The secular light-curves (SLCs) of comets C/2011 L4 Panstarrs and C/2012 S1 ISON are plotted. The brightness of both comets increased steeply after discovery but decreased sharply at∼4–5 au, a characteristic of Oort Cloud cometary light-curves referred to as a slope discontinuity event (SDE). After the SDE, the SLC of C/2011 L4 continued to increase and had a surge near perihelion. The SLC of comet C/2012 S1 ISON, on the other hand, is very unusual and exhibits a SDE plus a near-standstill after the event. Five other comets with similar behaviour, namely C/1996 Q1 Tabur, C/1999 S4 LINEAR, C/2002 O4 H¨onig, C/2010 X1 Elenin and C/2012 T5 Bressi, are known, all of which disintegrated. Thus it is predicted that comet ISON will disintegrate too. Published production rates of water, dust and CO were compiled and used to calculate the mass-loss budget. This information was used for ISON to calculate the diameter and to plot 29 comets in an evolutionary diagram that separates comets by class. A diameter D = 1030 ± 70m was found, in excellent agreement with the upper limit found by Delamere and colleagues, D(mean) < 1126 m. It is evident that the SLCs exhibit complexity beyond current scientific understanding. Note: the comet disintegrated as predicted (CBET 3731) while this paper was being refereed.